Survey of MARS: Spatial Link Quality and Node Positioning in Wireless Relay Network (International Journal of Engineering and Computer Science, 2014)
Multihop wireless relays can extend the area of network connectivity instantly and efficiently. However, due to the spatialdependence of wireless link-quality, the deployment of relay nodes requires extensive, expensive measurement, and managementefforts. This paper presents a mobile autonomous router system, (MARS) through which a relay router autonomously seeks andadjusts the best “reception” position for itself and cooperatively forms a string-type relay network with other neighboring routers.Specifically, MARS 1) accurately characterizes spatial link-quality through a new measurement technique, 2) effectively probes/optimizes node positioning via a spatial probing algorithm, and 3) maintains error-tolerant position information via an inexpensivepositioning algorithm. MARS has been prototyped with both a commodity mobile robot and a wireless router with IEEE 802.11cards. Our experimental evaluation of both the MARS prototype and ns-2-based simulation show that MARS achieves an average of 95 percent accuracy in link-quality measurements, and reduces the measurement effort necessary for the optimization of a node’slocation by two-thirds, compared to exhaustive spatial probing